2017
DOI: 10.1007/s10803-017-3446-0
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Links Between Challenging Behaviors in Youth with ASD and Parental Stress, Mental Health, and Involvement: Applying an Adaptation of the Family Stress Model to Families of Youth with ASD

Abstract: Raising a child with autism spectrum disorder (ASD) poses unique challenges that may impact parents' mental health and parenting experiences. The current study analyzed self-report data from 77 parents of youth with ASD. A serial multiple mediation model revealed that parenting stress (SIPA) and parental mental health (BAI and BDI-II) appears to be impacted by challenging adolescent behaviors (SSIS-PBs) and, in turn, affect parental involvement (PRQ), controlling for social skills (SSIS-SSs). Further, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 75 publications
(74 reference statements)
1
32
0
Order By: Relevance
“…Furthermore, the psychological stress caused by improving children’s school readiness also encouraged parents to recklessly adopt more radical measures to enhance their children’s academic achievement to demonstrate their children’s abilities. This finding is consistent with previous research indicating that parents’ psychological status is an essential factor affecting parental involvement (Paulson et al, 2011 ; Schiltz et al, 2018 ). According to the spillover hypothesis theory, certain emotions or behaviors (positive or negative) of family members in a family system are transferred from one situation to another (Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the psychological stress caused by improving children’s school readiness also encouraged parents to recklessly adopt more radical measures to enhance their children’s academic achievement to demonstrate their children’s abilities. This finding is consistent with previous research indicating that parents’ psychological status is an essential factor affecting parental involvement (Paulson et al, 2011 ; Schiltz et al, 2018 ). According to the spillover hypothesis theory, certain emotions or behaviors (positive or negative) of family members in a family system are transferred from one situation to another (Wang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…Second, the Abidin’s parenting stress model emphasizes the impact of child difficulties on the parent distress [ 43 ]. Parenting stress manifests when perceptions of parenting needs are not compensated by enough parental support [ 44 ]. When children have mental health symptoms, parents may face numerous stressors, including adjustments to their children’s internalizing and externalizing problems; a resulting incongruence between perceptions of demands and expected supports may, in turn, raise parenting stress, known to be associated with higher psychological distress [ 19 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoo et al [ 25 ] examine the use of a parent-assisted social skills training program for teens with ASD which was shown to be effective in improving social skills of adolescents in North America. Schiltz et al [ 26 ] examined the link between the challenging behaviour of youth with ASD and parental stress and involvement and found that stress has a negative impact on parental involvement, motivating the need to consider the whole family system in research on young people with ASD.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, there is a need to reveal how young children are supported. It is noticeable in the literature that studies about parents’ involvement or experiences are often related to older children and adolescents, high school pupils and adolescents [ 25 , 26 , 29 ] students [ 22 , 27 ] older children between the ages of 9 and 14. There have been few studies that have considered much younger children, however, these studies also included adolescents and adults [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation